ENVIRONMENTAL HEALTH REGULATIONS IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW OF AIR-WATER-SOIL POLLUTION CONTROL, MEDICAL AND HAZARDOUS WASTE MANAGEMENT, AND OCCUPATIONAL SAFETY IN HEALTH FACILITIES TO ACHIEVE A SUSTAINABLE ENVIRONMENT - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2026)
This article   analyses environmental health regulations in Indonesia, focusing on the regulation of air, water and soil pollution from health facilities, medical and hazardous waste management, and SMK3RS occupational safety standards to achieve a sustainable environment. The main findings reveal the normative strength of Law No. 32/2009, Government Regulation No. 22/2021, and Minister of Health Regulation No. 52/2018, which are comprehensive but poorly implemented with only 60% compliance due to a lack of digital monitoring and inter-ministerial synergy. Therefore, the study of these two main issues formulates recommendations for reforms based on AI-GIS, plasma pyrolysis technology, and green PROPER for an ecocentric transformation aligned with SDGs 3, 6, 11, 12.